If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12m+9-2m-16=0
We simplify the equation to the form, which is simple to understand
12m+9-2m-16=0
We move all terms containing m to the left and all other terms to the right.
+12m-2m=0-9+16
We simplify left and right side of the equation.
+10m=+7
We divide both sides of the equation by 10 to get m.
m=0.7
| x+2=-34+5x | | 230=2(3x-5)+2(5x+8) | | 100(4+x)=.75(8+x) | | 59+x=59 | | 7x+2=4x+29 | | 6a+10b-a+b= | | 7=-3x+5x-1 | | 6b+3=45 | | (3x-y)(x+2y)= | | X+51=50 | | 2m+4m-m=75 | | 3+10x+3x^2=0 | | 50=6y+32 | | 57+x=85 | | 24x-8=8(3x-1) | | x^4-4x^3-2x^2-4x+1=0 | | 200x+30000=200 | | 4x(5x+2)=0 | | -4x-8+x=-8 | | -1=-1/1+b | | 16+5x=58+3x | | 9x^3+18x^2+6=0 | | 2x^2-6x-15=5 | | (2a+3b)(3b-2a)= | | 8d-3-3d=42 | | (n-6)*8=48 | | x-2+4x=18 | | 28v^2-11v+1=0 | | x+63=70 | | 5h-5k=20 | | 4x^2-27x+33=-4x+5 | | 7v^2+27v-4=0 |